Facile production of mesoporous WO3-rGO hybrids for high-performance supercapacitor electrodes: an experimental and computational study - Samal, Rutuparna; Chakraborty, Brahmananda; Saxena, Manav; Late, Dattatray J.; Rout, Chandra Sekhar (ACS Sustainable Chemistry & Engineering, 2019)
This work explored a promising supercapacitor electrode material (WO3-rGO hybrids) synthesized via a simplistic one-pot hydrothermal synthesis route. Various analytical studies (X-ray diffraction study, Raman spectroscopy, field emission scanning electron microscopy, transmission electron microscopy, X-ray photoelectron spectroscopy, Brunauer-Emmett-Teller analysis) were employed in furtherance to explore the structural, morphological, compositional, and surface areal properties of the prepared materials. The enhancement in electrochemical supercapacitive properties were evaluated from pure hexagonal phase WO3 to the various hybrids, depending on the concentration of GO introduced into it, using cyclic voltammetry, galvanostatic charge/discharge, and electrochemical impedance spectroscopy. The WG-80 composite revealed the high rise in capacitance value of 801.6 F/g overcoming the individual capacitance of rGO (71.11 F/g) and WO3 (94.22 F/g) at a current density of 4 A/g with good cycling stability (75.7%) over 5000 cycles. We have presented quantum capacitance from ab initio calculations and provided theoretical explanation from the orbital interactions.
Keywords: Density functional theory; Hydrothermal method; supercapacitor; WO3-rGO hybrids

Co-decorated tellurium nanotubes for energy storage applications - Bhol, Prangya; Swain, Swarnalata; Jena, Satyaranjan; Bhatte, Kushal; Rout, Chandra Sekhar; Saxena, Manav; Jadhav, Arvind H.; Samal, Akshaya K. (ACS Applied Nano Materials, 2021)
This paper explicitly discusses the synthesis of Co-decorated Te nanotubes (NTs) using Te NTs as the sacrificial template and the evaluation of their electrochemical performance. First, one-dimensional (1D) Te NTs were synthesized and characterized by spectroscopic and microscopic tools such as UV-visible spectroscopy, X-ray diffraction spectroscopy, X-ray photoelectron spectroscopy, field-emission scanning electron microscopy, high-resolution transmission electron microscopy, and energy-dispersive X-ray spectroscopy analyses. The as-prepared hexagonal Te NTs (h-Te NTs) possess diameters of about 35 +/- 5 nm and lengths of about 500 +/- 50 nm and were used for the synthesis of Co-decorated Te NTs. The 1D nanostructure with excellent conductivity enables the material to show excellent electrochemical performance. The asymmetric assembly of the CoTe-2//AC electrode material displayed a high specific capacitance of 147 F g(-1) (specific capacity, 162 C g(-1) at a current density of 2 A g(-1) in 4 M KOH electrolyte. In addition to that, the assembly of CoTe-2//AC achieved an excellent energy density of 51.1 W h kg(-1) at a power density of 2294 W kg(-1) and confirmed the as-synthesized Co-decorated Te NTs to be an excellent electrode material.
Keywords: cobalt; nanotubes; pseudocapacitors; surfactant; Tellurium; template